Formation and Decay of Exotic Nuclear System using Energy Density Formalism - Sharma, Manoj Kumar (Sponsored by University grant commission, New Delhi, 2012)
abstract attached
Final Report/Executive summary
Keywords: compound nucleus, Energy density formalism